Training Activity Program in Teacher Competency Development Marasa Ibtidaiyah - Mukhoiyaroh, Mukhoiyaroh; Mujiono, Mujiono; Mukaromah, Lailatul (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2025)
Competency development for teachers is a necessary task that every teacher should undertake. Teacher competency development is intended to enhance teachers' skills and support the smooth execution of tasks. MIN 1 Mojokerto can continue to a higher level of education, whether it is above the current level or the next, whether public or private. These skills are not spared by the teacher competency development training activities that have been provided to teachers, which then have a positive impact on the learning provided to students, resulting in increased learning outcomes. Based on the explanation above, the researcher developed the research title